HOPE AND SACRIFICE IN THE SHORT STORY 'THE LAST LEAF’ BY O. HENRY - Aisha, Shazfa Q.; Mahi M. Hkikmat, Mahi M. (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2024)
This research explores the themes of hope and sacrifice using William Wordsworth's romanticism theory to analyse the themes of hope and sacrifice in O. Henry's short story